Peranan Credit Union dalam Mengatasi Persoalan Sosial Ekonomi di Kabupaten Kepulauan Tanimbar (Studi Kasus pada Credit Union Hati Amboina Saumlaki) - Martinus Lukas Kamamas; Petrus Balak; Titus Odong Kusumajati (EXERO : Journal of Research in Business and Economics, 2019)
This study aims to examine the role of Hati Amboina Credit Union in resolving the problem of poverty faced by members. This study uses a qualitative approach with the triangulation method. The subjects of this study were 100 active members of the Credit Union, 3 (three) administrators, and 2 (two) government officials from the government office of cooperatives. The research data were analyzed by classifying the data based on the variety of data and information obtained from literature, documents, surveys, interviews and field observations. The results of this study indicate that the presence of Hati Amboina Credit Union in Saumlaki is able to resolve socio-economic problems experienced by members. The model applied by Hati Amboina Credit Union to resolve the members' problems was encouraging members to take advantage of all loan and savings products as well as an empowerment approach to each business and non-business basis community. However, the achievement of Hati Amboina Credit Union was not at its maximum level due to the influence of the Covid-19 pandemic.